1988
DOI: 10.1161/01.hyp.11.6.573
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-dependent responses in carotid and renal arteries of normotensive and hypertensive rats.

Abstract: SUMMARY Endothelium-dependent relaxations are impaired in the aorta of various models of hypertension, but no data are available regarding the cerebral or renal circulation. Endotheliumdependent relaxations were studied in the carotid and renal artery of Wistar-Kyoto rats (WKY) and spontaneously hypertensive rats (SHR). Rings with and without endothelium were suspended in organ chambers for isometric tension recording. Acetylcholine and adenosine 5'-diphosphate (ADP) caused endothelium-dependent relaxations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
3
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(61 citation statements)
references
References 15 publications
5
52
3
1
Order By: Relevance
“…These findings are consistent with a previous report by Luscher et aJ. 17 Morphological evaluation of the three arteries showed a regional distribution of the subendothelial infiltration with monocyte macrophages similar to the regional distribution of endothelial dysfunction. Indeed, the number of subendothelial cell nuclei in SHR was highest in the carotid artery, less in the aorta, and very low in the renal artery.…”
supporting
confidence: 93%
“…These findings are consistent with a previous report by Luscher et aJ. 17 Morphological evaluation of the three arteries showed a regional distribution of the subendothelial infiltration with monocyte macrophages similar to the regional distribution of endothelial dysfunction. Indeed, the number of subendothelial cell nuclei in SHR was highest in the carotid artery, less in the aorta, and very low in the renal artery.…”
supporting
confidence: 93%
“…The acetylcholine dose-response curve for afferent arterioles from 2K1C rats was shifted to the right compared with vessels from SHAM animals; however, these vessels were equally responsive to a high concentration of the endothelium-independent vasodilator sodium nitroprusside. Our observations contrast with those of Luscher et al, 3 who reported that endothelium-dependent relaxations induced by acetylcholine and ADP were identical in renal artery rings from spontaneously hypertensive and Wistar-Kyoto rats. This discrepancy may be due to the models of hypertension used, the different experimental settings under which the vasculature was studied, or a distinction between the integrity of endothelium-dependent function at the macrovascular versus microvascular level in the normal or hypertensive kidney.…”
Section: Discussioncontrasting
confidence: 99%
“…4,6,18,44 Actually, the existence of endothelium-dependent contractions and their exacerbation under pathological conditions have been demonstrated not only in aortas but also in smaller arteries. [45][46][47] Studies on human forearm microcirculation in healthy subjects and hypertensive patients further provide evidence that the production of EDCF contributes to the endothelial dysfunction with aging and hypertension. 48,49 These findings presumably permit the extrapolation of the effect of hemin observed in the present study on the endothelium of the aorta to that of the resistance arteries.…”
Section: Limitationsmentioning
confidence: 99%